2021
DOI: 10.1590/1676-0611-bn-2020-1004
|View full text |Cite
|
Sign up to set email alerts
|

Foraging preferences of the native stingless bee Melipona seminigra pernigra (Apidae: Meliponini) in campo rupestre on canga of Serra dos Carajás, southeastern Amazonia

Abstract: Honey pollen samples of Melipona seminigra pernigraMoure & Kerr 1950 sampled between 2017 and 2019 from experimental apiaries installed in campo rupestre on canga (CRC) vegetation of the Serra dos Carajás aimed to evaluated seasonal floral availability of undisturbed and mining-influenced areas. Around one hundred pollen types were identified mainly belonging to Fabaceae, Myrtaceae and Euphorbiaceae (31, 6 and 5 species, respectively). Mining area presented the highest pollen richness, almost twice those i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Studies conducted in 18 colonies of three species of the Meliponini tribe found a prevalence of small pollen grains, suggesting the preference of these bees for small-size flowers with short pistils (Vossler, 2015). Guimarães et al (2021) studies confirm the results obtained in the Mayabeque honey regarding the abundance of M. pudica pollen grains (10 µm). These authors detected high representativeness of the Mimosa type in the pollen content of honey samples of Melipona seminigra pernigra Moure andKerr, 1950, ascribable, according to Ferreira andAbsy (2017), to its release in large quantities, their configuration, and the small size of pollen grains (Zappi et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Studies conducted in 18 colonies of three species of the Meliponini tribe found a prevalence of small pollen grains, suggesting the preference of these bees for small-size flowers with short pistils (Vossler, 2015). Guimarães et al (2021) studies confirm the results obtained in the Mayabeque honey regarding the abundance of M. pudica pollen grains (10 µm). These authors detected high representativeness of the Mimosa type in the pollen content of honey samples of Melipona seminigra pernigra Moure andKerr, 1950, ascribable, according to Ferreira andAbsy (2017), to its release in large quantities, their configuration, and the small size of pollen grains (Zappi et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, even the Convolvulaceae pollen are common on bee honeys [ 14 ], lake surface sediments [ 15 , 16 ], and Quaternary lake cores [ 17 , 18 ]. However, these studies unfortunately made a genus-level identification.…”
Section: Introductionmentioning
confidence: 99%